Credit card debt puzzles - Michael Haliassos; Michael Reiter (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
Most US credit card holders revolve high-interest debt, often combined with substantial (i) asset accumulation by retirement, and (ii) low-rate liquid assets. Hyperbolic discounting can resolve only the former puzzle (Laibson et al., 2003). Bertaut and Haliassos (2002) proposed an 'accountant-shopper' framework for the latter. The current paper builds, solves, and simulates a fully-specified accountant-shopper model, to show that this framework can actually generate both types of co-existence, as well as target credit card utilization rates consistent with Gross and Souleles (2002). The benchmark model is compared to setups without self-control problems, with alternative mechanisms, and with impatient but fully rational shoppers.
urn:nbn:de:hebis:30-23385
Keywords: E21; G11; 330; Credit Cards; Debt; Self Control; Household Portfolios; Kreditkarte; Schulden; Theorie